Subclinical infection of hepatitis E and its influencing factors among community residents in Shanghai - Zheng-bin XIAO; Kai-yun CHEN; Lin WANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate the prevalence and influencing factors of subclinical infection of hepatitis E virus (HEV) in Shanghai community residents for providing evidences to comprehensive prevention and treatment of hepatitis E.MethodsWith multistage probability proportional-to-size random sampling, we conducted a seroepidemiological survey among 4 661 permanent residents (aged 1 - 69 years) in 32 urban communities/rural villages in 16 districts of Shanghai city during May - December 2018. The participants had face-to-face interviews with a self-designed questionnaire and detections of serum HEV immunoglobulin G (IgG) and immunoglobulin M (IgM) by enzyme-linked immunosorbent assay (ELISA). Binary multivariate logistic regression analysis was adopted to explore influencing factors of subclinical HEV infection.ResultsOf all the participants, 26.11% (1 217) were positive for HEV-IgG or HEV-IgM antibody. The results of regression analysis revealed that the risk factors of subclinical HEV infection included male gender, five years old and above, drinking unboiled water occasionally, being retired, having hepatitis related detection during past six months, and consuming fresh sashimi during past six months; the results also showed that with a non-local registered residence, being not sure about a history of having HEV vaccination, and washing hands before eating and after using bathroom were protective factors against HEV infection.ConclusionAmong urban and rural community residents of Shanghai city, the prevalence of HEV subclinical infection was relatively high and influenced mainly by gender, age, occupation, registered residence, whether drinking unboiled water, history of HEV vaccination, and the status of having hepatitis-related test/consuming fresh sashimi during past six months.